Haematological parameters in rats treated with royal jelly and curcumin antioxidants after CCL4haemotoxicity - Ahmed, Marawan; G, ABDELRACHIED H (JOURNAL OF ADVANCES IN BIOLOGY, 2015)
The aim of the present work is to explore the possible effect of royal jelly and curcumin on CCL4 intoxicated albino rats. Concerning haematological parameters (RBCs count ,WBCs count , Hb content , HCT value and blood indices ( MCV,MCH and MCHC ) values ,lymphocytes percentage and monocytes percentageÂ  in rats injected with CCL4 for four and six weeks . The results referred to a significant decrease in RBCs count , Hb content , HCT , MCV , MCH values and lymphocytes percentageÂ  in rats injected with CCL4 at four and six weeks. While rats treated with oral administration of royal jelly and cur cumin after CCL4 injection recorded improvementsin red blood cells and hemoglobin content. On the other hand a significant increase in WBCs count and monocytes percentage were recorded in rats injected with CCL4 at four and six weeks.